REN’PY як засіб розробки мультимедійних видань - Роскошна, А. В.; Шипова, М. К. (ХНУРЕ, 2025)
This article examines Ren’Py as a tool for developing multimedia publications in the format of interactive narratives. It explores the engine’s structure, key components, and scripting capabilities, highlighting its advantages for creating nonlinear stories. The paper discusses the accessibility of Ren’Py for users with minimal programming experience, its built-in debugging tools, and support for cross-platform development. Attention is also given to the engine’s limitations, particularly its focus on 2D static images and text-driven interaction, as well as the challenges of expanding its functionality beyond visual novels. The study evaluates the potential of Ren’Py for adapting literary works into digital formats and considers its suitability for experimental multimedia projects.
Keywords: мультимедійне видання; multimedia publication